Modern methods of monitoring and assessing the current status of athletes-combatants in real time - Puhach, Y.; Druz, V.; Yefremenko, A.; Revenko, V.; Galashko, M.; Shutieiev, V.; Nizhevskaya, T.; Miroshnichenko, V. (Slobozhanskyi herald of science and sport, 2019)
Purpose: to establish the most effective methods of monitoring and evaluating the current status of athletes, and on the basis of this, develop methods for remote monitoring of the current state of martial arts in the process of conducting a duel.